Linguistic justice and the challenge of immigration. Issue 2 (13th January 2022) - Milioni, Anna; Pappas, Athanasios
Abstract: The contemporary conditions of migration and transnational mobility raise important questions regarding linguistic justice. Immigrants and national populations claim to have multiple and often conflicting linguistic entitlements. In this paper, we account for a fair allocation of linguistic rights in this migratory context. First, we distinguish between instrumental and non‐instrumental language interests, and we argue against the position that linguistic rights can be waived upon migration. Then, we examine two popular approaches of linguistic justice: the linguistic territoriality approach and the linguistic personality approach. As we demonstrate, these approaches present shortcomings when dealing with the linguistic claims of immigrants, failing to accommodate important aspects of their interests. We argue that the fair accommodation of these interests requires the recognition of English as an official national language, by virtue of its role as the global lingua franca. We then try to dispel some objections that could be raised against our approach.